Child feeding practices in a rural Western Kenya community - Grace M. Mbagaya (AOSIS, 2009)
Background: Breastfeeding is nearly universal in Kenya. However, supplementation of breast milk starts too early, thereby exposing the infants to diarrhoea and other infections. Despite the recommendation of the World Health Organization (WHO) of exclusive breastfeeding (EB) from birth to six months, EB is rare and poorly timed and complementary feeding (CF) practices are still common. The study describes feeding practices of children aged 0 to 24 months in the Mumias Division of the Kakamega district in Kenya. Method: Using a cross-sectional study, 180 mothers of infants/children were interviewed using a structured questionnaire. Data on socio-demographic characteristics, feeding practices and sources of information on the same were obtained from the mothers. Results: Whereas 92.1% of the children were breastfed, only 12.2% of the mothers practiced EB up to 4 to 6 months. Mothers introduced liquids and complementary foods at a mean age of 2.7 months and by the fourth month, more than one-third (34.5%) of the mothers had initiated CF. Apart from water, fresh milk, tea, commercial juices, maize-meal/millet porridge, mashed potatoes, bananas and fruits were also introduced. The perceived reasons for introducing these foods included the child being old enough (33.8%), another pregnancy (25%), insufficient milk (20.3%), sickness of the mother or child (10.5%) and in order for the child to eat other foods (11.4%). Over half (53.3%) of the mothers obtained information on BF and CF from friends, neighbours, media advertisements and health workers. Conclusion: Breastfeeding is common; however, mothers do not seem to practice the WHO recommendations. Mothers in this study area and other rural communities need to be empowered with information on the correct BF and CF practices through existing government health services, nongovernmental organisations and other community-based networks, especially in the light of the HIV/AIDS pandemic.